Widening, transition and coalescence of local resonance band gaps in multi-resonator acoustic metamaterials: From unit cells to finite chains. (14th April 2022) - Stein, A.; Nouh, M.; Singh, T.
Abstract: Local resonance band gaps in acoustic metamaterials are widely known for their strong attenuation yet narrow frequency span. The latter limits the practical ability to implement subwavelength band gaps for broadband attenuation and has motivated novel metamaterial designs in recent years. In this paper, we investigate the behavior of acoustic metamaterials where unit cells house multiple resonating elements stacked in different configurations, aimed at instigating a wide array of wave propagation profiles that are otherwise unattainable. The dispersion mechanics of the multi-resonator metamaterials are developed using purely analytical expressions which depict and explain the underlying dynamics of such systems both at the unit cell level as well as the frequency response of their finite realizations. The framework reveals the mechanism behind the transition of the lower and upper band gap bounds in metamaterials with parallel resonators resulting in a significant band gap widening. The analysis also illustrates the ability of metamaterials with dual-periodic super cells to exhibit a range of dispersion transitions culminating in collapsing solutions of acoustic and optical bands, enabling a coalescence of local resonance band gaps, vanishing resonances, and a number of intriguing scenarios in between. Highlights: Dispersion mechanics of multi-resonator metamaterials are analytically derived. Band gap widening in parallel-resonator finite metamaterials achieved via shorter chains. Band gap coupling and transition in dual-periodic super cells is fully explained. Coalescence of local resonance band gaps with single and double attenuation peaks.